Results of Teacher’s Supervision at SDN 6 Banyuasin I - Gunardi, Ahmad (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
The implementation of academic supervision is a professional guidance activity carried out by the principal to teachers to ensure that they can carry out their teaching obligations with high performance so that learning can run effectively with the main indicators being an active, creative, inventive, effective, efficient, and enjoyable learning process. This study aims to determine the implementation of academic supervision to improve teacher performance. This type of research is a literature study. using conceptual and theoretical research. The literature study uses 30 journals as study materials. The stages in writing a literature study include topic selection, literature search, opinion development, literature survey, literature criticism, and review writing. The results of the study state that academic supervision which runs effectively can improve teacher performance, especially in carrying out learning activities. The implementation of effective academic supervision is carried out starting from activity planning, implementation, providing feedback, and following up. The tools for carrying out assessments in implementing academic supervision include learning device administration assessment instruments, lesson plan assessment instruments, learning implementation assessment instruments, learning evaluation assessment instruments, follow-up instruments, and overall performance assessment instruments.